Pengaruh Non Performing Loan dan Good CorporateGovernance Terhadap Nilai Perusahaan di Sektor Perbankan - Asep Saeful Falah; Tantri Wijaya (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the effect of Non-Performing Loans (NPL) and Good Corporate Governance (GCG) on company value in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2012–2022. Using a purposive sampling method, 3 bank samples with a total of 33 data were obtained and analyzed using multiple linear regression with SPSS 26. The results showed that BBCA had the smallest NPL ratio, and BMRI was the company with the highest GCG score. Meanwhile, the increase in BBCA's Company Value (PBV) had the highest PBV ratio of the 3 research banks. The results of the partial hypothesis test showed that NPL had a significant negative effect on company value as proxied by Price to Book Value (PBV), meaning that an increase in NPL decreased PBV. GCG had a significant effect on PBV, indicating that the implementation of good GCG principles can increase stakeholder trust and company value. Simultaneously, NPL and GCG had a significant effect on company value. The Adjusted R-Squared value of 73.8% can explain the company value variable.